Medical entomology for students - Service, M. W. (Cambridge University Press, 2012)
The fifth edition of this popular textbook is completely updated, and incorporates the latest strategies for controlling insects, ticks and mites. Clearly presented in a concise style, this text is aimed at students of medical entomology, tropical medicine, parasitology and pest control.